2017
DOI: 10.1186/s12870-017-1094-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of flowering genes in leaves of ‘Pineapple’ sweet orange [Citrus sinensis (L.) Osbeck] and pummelo (Citrus grandis Osbeck)

Abstract: BackgroundIn citrus the transition from juvenility to mature phase is marked by the capability of a tree to flower and fruit consistently. The long period of juvenility in citrus severely impedes the use of genetic based strategies to improve fruit quality, disease resistance, and responses to abiotic environmental factors. One of the genes whose expression signals flower development in many plant species is FLOWERING LOCUS T (FT).ResultsIn this study, gene expression levels of flowering genes CiFT1, CiFT2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In kumquat and trifoliate orange, an increase in the expression levels of CiFT2 was observed during early summer, during (or just before) the onset of the flower organs [48]. Similar results were observed in pummelo (C. grandis Osbeck) and "Pineapple" sweet orange by Pajon et al [52], suggesting that the increase in CiFT gene expression soon after flowering is probably associated with changes in light conditions or internal signal regulation. Other factors could have played a role in the high expression levels recorded in July for TS/SC; among these are the increased solar radiation availability and the water-deficit stress induced by the very high evaporative demand during summer, even in irrigated plants.…”
Section: Discussionsupporting
confidence: 74%
“…In kumquat and trifoliate orange, an increase in the expression levels of CiFT2 was observed during early summer, during (or just before) the onset of the flower organs [48]. Similar results were observed in pummelo (C. grandis Osbeck) and "Pineapple" sweet orange by Pajon et al [52], suggesting that the increase in CiFT gene expression soon after flowering is probably associated with changes in light conditions or internal signal regulation. Other factors could have played a role in the high expression levels recorded in July for TS/SC; among these are the increased solar radiation availability and the water-deficit stress induced by the very high evaporative demand during summer, even in irrigated plants.…”
Section: Discussionsupporting
confidence: 74%
“…Three FT homologs have been identified in the satsuma mandarin ( Citrus unshiu ). Among the three, the FT1 and FT2 are considered alleles at the same locus 26 , 27 , and therefore, only FT1 and FT3, was used in this study (Supplementary Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…They observed that the expression level of three genes was at peak during the month of April and subsided after that regardless of the conditions in which they were growing (protected or open field conditions). In C. unshiu , three FT transcripts, CiFT1 , CiFT2 , and CiFT3 have been identified and characterized [ 75 , 162 ] of which CiFT1 and CiFT2 are isoforms encoded by the same gene [ 163 ] and CiFT3 is considered a better floral-inductive treatment compared to CiFT1 and CiFT2 [ 164 , 165 ]. Soares et al [ 108 ] developed transgenic “Carrizo” citrange hybrid using CcFT1 and CcFT3 (homologs of FT in C. clementine ).…”
Section: Discussionmentioning
confidence: 99%